A Novel Role of A2AR in the Maintenance of Intestinal Barrier Function of Enteric Glia from Hypoxia-Induced Injury by Combining with mGluR5 - Sun, Lihua; Li, Xiang; Guan, Haidi; Chen, Shuaishuai; Fan, Xin; Zhou, Chao; Yang, Hua; Xiao, Weidong (Frontiers in Pharmacology, 2021)
During acute intestinal ischemia reperfusion (IR) injury, the intestinal epithelial barrier (IEB) function is often disrupted. Enteric glial cells (EGCs) play an important role in maintaining the integrity of IEB functions. However, how EGCs regulate IEB function under IR stimulation is unknown. The present study reveals that the adenosine A2A receptor (A2AR) is important for mediating the barrier-modulating roles of EGCs. A2AR knockout (KO) experiments revealed more serious intestinal injury in A2AR KO mice than in WT mice after IR stimulation. Moreover, A2AR expression was significantly increased in WT mice when challenged by IR. To further investigate the role of A2AR in IEB, we established an in vitro EGC-Caco-2 co-culture system. Hypoxia stimulation was used to mimic the process of in vivo IR. Treating EGCs with the CGS21680 A2AR agonist attenuated hypoxia-induced intestinal epithelium damage through up-regulating ZO-1 and occludin expression in cocultured Caco-2 monolayers. Furthermore, we showed that A2AR and metabotropic glutamate receptor 5 (mGluR5) combine to activate the PKCα-dependent pathway in conditions of hypoxia. This study shows, for the first time, that hypoxia induces A2AR-mGluR5 interaction in EGCs to protect IEB function via the PKCα pathway.